PERSEPSI PETANI TERHADAP REGENERASI PETANI MUDA DI ERA MODERN (STUDI KASUS DI KABUPATEN BOJONEGORO) - Wijayanti, Kiki Rini; Sugiyanto, Sugiyanto; Nugroho, Tri Wahyu (Agros Journal of Agriculture Science, 2024)
This research aims to describe farmers' perceptions of the young farmer regeneration crisis in the modernization era, the challenges and difficulties faced by young farmers, develop policy recommendations and solutions to overcome the young farmer regeneration crisis and advance rural agriculture in Bojonegoro Regency. The method used is the Mix Method by combining qualitative and quantitative. The population in this study were all farmers in Nguken Padangan Village, Bojonegoro, totaling 220 people with a perception sample of 142 farmers. Meanwhile, the sample measured the regeneration of 41 farmers using purposive sampling and snowball techniques. The research results showed that farmers' perception of young regeneration was still less than 40%. The challenge for young farmers is limited access to capital, technology and less skilled human resources. The difficulty faced is the lack of training and experience of the younger generation, agriculture currently does not promise prosperity for young people. Strategies that can be proposed include holding training on agricultural technology, providing subsidies, conducting outreach regarding more promising agricultural potential and providing counseling regarding financial management.